Economic aspects of aged apple plantations in Hungary - Apáti, F.; Felföldi, J. (International Journal of Horticultural Science, 2006)
Being competitive is a goal all over in the EU. Competition is free and getting closer among the competitors of the apple industry. In Hungary, one of the most important issues of apple industry has been what are the prospects for aged plantations, which account for 50% of crop land. Based on our results, 80% of those apple plantations on the down-grade yielding apple, the ones only for processing, do not meet the criteria of competitive production. For those plantations in better shape that yield 30-40 t/ha, of which at least 20-30% are for fresh production, it can he profitable. Because of the future trend in technology and economy, however, even the latter ones can not be considered being competitive in the long run.